2020
DOI: 10.1111/apha.13537
|View full text |Cite
|
Sign up to set email alerts
|

Th17/Treg imbalance modulates rat myocardial fibrosis and heart failure by regulating LOX expression

Abstract: Chronic heart failure (HF) is the final stage of many cardiovascular diseases and imposes a great health and economic burden on society and families due to its high morbidity and mortality [1]. Myocardial fibrosis is closely associated with almost all types of heart diseases, including HF [2]. Thus, there is an unmet need to develop novel and effective therapeutic strategies for alleviating myocardial fibrosis. The enzyme lysyl oxidase (LOX) is a copper-dependent extracellular enzyme that catalyzes lysine-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…In addition, IL-23 secreted by Th17 cells can promote the secretion of granulocyte-macrophage colony-stimulating factor by Th17 cells, in ltration of other immune cells, and a chronic in ammatory response (El-Behi et al 2011). An increase in Th17 cells is often accompanied by a decrease in Treg cells (Lu et al 2020), which is consistent with the results observed in this study. Therefore, we propose that VCAM1 promotes HF by regulating Th17 cell in ltration.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, IL-23 secreted by Th17 cells can promote the secretion of granulocyte-macrophage colony-stimulating factor by Th17 cells, in ltration of other immune cells, and a chronic in ammatory response (El-Behi et al 2011). An increase in Th17 cells is often accompanied by a decrease in Treg cells (Lu et al 2020), which is consistent with the results observed in this study. Therefore, we propose that VCAM1 promotes HF by regulating Th17 cell in ltration.…”
Section: Discussionsupporting
confidence: 93%
“… 23 The Th17/Treg imbalance also existed in patients with HFpEF. 24 Decreased Tregs were reported to aggravate myocardial fibrosis and HF, 25 and upregulation of Tregs could ameliorate cardiac dysfunction in chronic heart failure. 25 Our results also show that BHB treatment increased Treg cells and inhibited cardiac inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Decreased Tregs were reported to aggravate myocardial fibrosis and HF, 25 and upregulation of Tregs could ameliorate cardiac dysfunction in chronic heart failure. 25 Our results also show that BHB treatment increased Treg cells and inhibited cardiac inflammation. These results suggest that BHB not only serves as an energy fuel but also functions as an immunomodulatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme lysyl oxidase (LOX) upregulation is associated with vascular fibrosis ( Martinez-Gonzalez et al, 2019 ). A study has shown that Th17 and Treg might modulate LOX expression through their characteristic cytokines IL-17 and IL-10, respectively, thereby regulating fibrosis ( Lu et al, 2020 ). Taken together, the disruption of Treg/Th17 balance and gut microbiota-derived beneficial SCFA reduction are important parameters of the vascular fibrosis in AS.…”
Section: Introductionmentioning
confidence: 99%